GAYA KOMUNIKASI ATASAN & BAWAHAN DI DIVISI PERTANAHAN PT PARAMOUNT LAND (Studi Fenomenologi Komunikasi Vertikal di Tempat Kerja) - Hilda Adhanti (2020)
Organizational activities will run well if there is effective communication in it. If there is no communication employees will not know what work will be done and superiors can not accept suggestions, opinions, and can not provide job direction. Superiors must be able to apply the style of communication in accordance with the state of the organization in order to have a good impact on employee performance. This study discusses the style of superior & subordinate communication in the Land Division of PT Paramount Land (Study of the Phenomenology of Vertical Communication at Work). This study aims to determine and explain how the communication style of superiors and subordinates in the land division of PT. Paramount Land and to find out the impact of what happened in the development of superiors and subordinate communication styles in the land division of PT. Paramount Land. The models used in this study are Steward L. Tubbs Communication Style and Sylvia Moss (1998) Controlling Style, Equalitarian Style, Structuring Style, Dynamic Style, Relinguishing Style, Withdrawal Style. This research is a qualitative study using a phenomenological research approach. Data collection techniques using interview techniques, documentation and literature study. The results of the research conducted are superiors applying three types of communication styles, namely The Controlling Style (one-way communication), The Equalitarian Style (two-way communication), and The Dynamic Style (dynamic communication style). Effective two-way communication is done to improve performance while one-way and dynamic communication is less effective because employees feel uncomfortable if the employer applies the communication style.